Workplace Writing A Handbook for Common Workplace Genres and Professional Writing - Goins, Anna; Rauh, Cheryl; Tarner, Danielle; Von Holten, Daniel (Open textbook library., 2024)
This handbook is designed for a generalized business writing course that seeks to meet the needs of a variety of student majors and career interests. In it you will find: descriptions and discussions of common genres, both routine and formal, print and electronic, and in-class activities and sample assignments. You will also find commentary on how to adapt the writing process to the rhetorical constraints of a workplace as well as how to think about, conduct, and use research outside an academic setting. Throughout you will note a persistent emphasis on audience awareness and direct style